2007
DOI: 10.1128/jcm.00019-07
|View full text |Cite
|
Sign up to set email alerts
|

Long Persistence of Methicillin-Susceptible Strains of Staphylococcus aureus Causing Sepsis in a Neonatal Intensive Care Unit

Abstract: Molecular epidemiology of Staphylococcus aureus strains causing bacteremia in neonates during 2002 to 2005revealed seven clones, with four MSSA clones responsible for 80% of the cases. Some clones persisted or reappeared throughout the study. Three bacteremic clones were found colonizing health care workers (HCWs), particularly clone C, which was harbored by at least 15% of HCWs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Colonized HCWs have been responsible for S. aureus outbreaks in neonates 2 29 , 30 We found hands of 3 HCWs to be positive for MSSA, providing proof for at least transient MSSA hand carriage. Without systematic HCW screening, we cannot formally exclude the possibility that a colonized HCW acted as a point source.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Colonized HCWs have been responsible for S. aureus outbreaks in neonates 2 29 , 30 We found hands of 3 HCWs to be positive for MSSA, providing proof for at least transient MSSA hand carriage. Without systematic HCW screening, we cannot formally exclude the possibility that a colonized HCW acted as a point source.…”
Section: Discussionmentioning
confidence: 60%
“…HCWs and the environment are likely sources for neonatal S. aureus colonization 2 29 , 30 Hence, it is difficult to fully appraise the present findings. In very young infants, colonization with S. aureus of up to 40%, a level equal to our findings, seems to be physiological in the community 39 .…”
Section: Discussionmentioning
confidence: 94%
“…No ICU patient was colonized by tst -positive S. aureus strain upon admission, whereas 14 acquired it during their stay. Observed differences regarding ICU and non-ICU strains are probably due to the dissemination of ST30 clone among patients and ICU staff, since colonized healthcare workers have been responsible for S. aureus outbreaks—especially in neonatal ICUs, as reported [ 19 ]. This successful spread is reinforced by PFGE/ agr analysis, which revealed that type A/3 stratified to ST30 and carriage of tst gene is consistently present among MRSA since 2001, as well as in MSSA as found in the present study [ 20 ].…”
Section: Discussionmentioning
confidence: 97%
“…Outbreaks of methicillin-resistant S. aureus (MRSA) at the NICU are described and relatively easy to detect [15][16][17][18]. Meanwhile, the detection of methicillin-sensitive S. aureus (MSSA) outbreaks seems to be more difficult, excluding outbreaks in patients who suffer from a skin infection [19][20][21][22]. In this study, whole-genome sequencing (WGS), the typing method with the highest discriminatory power, was used to determine whether MSSA transmission and genetic makeup, contribute to the occurrence of neonatal S. aureus bacteremia.…”
Section: Introductionmentioning
confidence: 99%